2013
DOI: 10.2139/ssrn.2200837
|View full text |Cite
|
Sign up to set email alerts
|

The StoNED Age: The Departure into a New Era of Efficiency Analysis? – A Monte Carlo Comparison of StoNED and the 'Oldies' (SFA and DEA)

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…SFA is parametric and DEA is deterministic (no meaningful error term), so a main advantage of SFA's regression based structure over DEA is its ability to consider statistical noise. It also is less sensitive to outliers than DEA (Andor & Hesse, ). A disadvantage relative to DEA is that, because it is regression based, SFA is limited to one output.…”
Section: Methodsmentioning
confidence: 99%
“…SFA is parametric and DEA is deterministic (no meaningful error term), so a main advantage of SFA's regression based structure over DEA is its ability to consider statistical noise. It also is less sensitive to outliers than DEA (Andor & Hesse, ). A disadvantage relative to DEA is that, because it is regression based, SFA is limited to one output.…”
Section: Methodsmentioning
confidence: 99%
“…Their analysis revealed that a substantial number of studies utilised sample sizes smaller than 80. Concurrently, Andor and Hesse (2011) observed that with a minimum sample size of 50, the SFA method demonstrated significantly improved performance.…”
mentioning
confidence: 86%
“…The study involved a total of 80 respondents, 3 a sample size deemed sufficient to achieve the objectives, as supported by the arguments in relevant literature (Andor & Hesse, 2011;Coelli, 1993;Thiam et al, 2001).…”
Section: Mohd Khairul Hafifi Maidin Roslina Kamaruddin and Shri Dewi ...mentioning
confidence: 99%
“…Our focus in this paper is on the concave least squares (CLS) problem under monotonicity assumption (MCLS). 2 One of the applications of this problem is to estimate a non-parametric production function that is monotonic and concave (Andor & Hesse, 2014;Cheng, Bjørndal, & Bjørndal, 2014;Eskelinen & Kuosmanen, 2013;Keshvari & Kuosmanen, 2013;Kuosmanen, 2011Kuosmanen, , 2012Wang, Wang, Dang, & Ge, 2014).…”
Section: Penalized Monotonic Concave Least Squaresmentioning
confidence: 99%